Tungsten doping of Ta3N5-nanotubes for band gap narrowing and enhanced photoelectrochemical water splitting efficiency - Grigorescu, Sabina Georgiana; Bärhausen, Benedikt; Wang, Lei; Mazare, Anca Valentina; Yoo, Jeong Eun; Hahn, Robert; Schmuki, Patrik (Electrochemistry Communications, 2015)
Ordered W-doped Ta2O5 nanotube arrays were grown by self-organizing electrochemical anodization of TaW alloys with different tungsten concentrations and by a suitable high temperature ammonia treatment, fully converted to W:Ta3N5 tubular structures. A main effect found is that W doping can decrease the band gap from 2 eV (bare Ta3N5) down to 1.75 eV. Ta3N5 nanotubes grown on 0.5 at.% W alloy and modified with Co(OH)x as co-catalyst show 33% higher photocurrents in photoelectrochemical (PEC) water splitting than pure Ta3N5.
EAM Import::2019-03-13